PERILAKU IBU DALAM PENANGGULANGAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS 4 ULU PALEMBANG 4 ULU - Dian Emiliasari (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
Based on WHO, diarrhea kills about 2 million children in the world each year. Referring to Palembang health service in 2017, the number of diarrhea suspects reached 48.000 people. Meanwhile, diarrhea cases tend to increase in the working areas of a community health center 4 Ulu Palembang every year. In 2016, there were about 1.341 children suspected of diarrhea and increased to 1.361 in 2017. This research aims to know about mothers' behavior using the descriptive method. Variables include the mother’s knowledge, attitudes, and actions in dealing with children under five years with diarrhea. This thesis will be developed based on primary and secondary data. Data will be analyzed with univariate statistics. The analysis shows that 62% of respondents have good knowledge, 58% have a good attitude, and 64% have done proper action in caring for children under five years with diarrhea in community health center 4 Ulu working area 2018. Based on the result, there are many mothers who didn’t have good knowledge and attitude in care of children under five years with diarrhea in working area community health center. It’s suggested that intensive promotion is necessarily given which integrating society participation. To learn more factors influencing a mother’s behavior in caring for children under five years with diarrhea needs further research.                                               Keywords: Diarrhea, TheChildren Under The Age of Five